Evaluasi dan Penilaian Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) pada Industri Konstruksi PT. Z - Muh Satria Arhamza; Yayok Suryo Purnomo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Management of Hazardous and Toxic Waste (B3) is an important aspect in supporting sustainable development while minimizing negative impacts on the environment. This research evaluates B3 waste management at PT. Z, a construction company that plays an important role in the production and maintenance. Evaluations are carried out on technical and non-technical aspects, including waste identification, temporary storage, transportation, and compliance with regulations such as PP Number 22 of 2021 and other related regulations. The research method uses a quantitative and qualitative approach, with primary data obtained through field observations, interviews and documentation, while secondary data includes SOPs, waste balances and logbooks. The analysis was carried out using a checklist and scoring method based on the Guttman scale to assess the level of compliance of B3 waste management with regulations. The research results show that B3 waste management at PT. The Z already meets most technical and regulatory standards with some aspects requiring improvement. This research is expected to provide an overview of the conditions of B3 waste management at PT. Z as well as relevant recommendations to increase management effectiveness, support regulatory compliance, and encourage the achievement of sustainable development goals.